Circulating Insulin-like Growth Factor-1 and Insulin-like Growth Factor Binding Protein-3 predict Three-months Outcome after Ischemic Stroke - Armbrust, Moritz; Worthmann, Hans; Dengler, Reinhard; Schumacher, Helmut; Lichtinghagen, Ralf; Eschenfelder, Christoph Cyrill; Endres, Matthias; Ebinger, Martin (Experimental and Clinical Endocrinology & Diabetes, 2017)
Reports on neuroprotective effects of Insulin-like growth factor-1 (IGF-1) and Insulin-like growth factor binding protein-3 (IGFBP-3) in ischemic brain tissue are inconsistent. The aim of this study was to determine if plasma levels of IGF-1 and IGFBP-3 in acute stroke patients are indicative of 3 months functional outcome. Plasma levels were measured via chemiluminescence immunoassay in heparin blood samples of patients included in the EARLY trial (NCT00562588). Plasma samples were drawn on admission and 8 days post-stroke. Neurological deficits were assessed via modified Rankin Scale (mRS) 3 months post-stroke, resulting in favorable (mRS=0–2) or unfavorable (mRS=3–6) outcome. A multiple binary logistic regression including IGF-1 and IGFBP-3 levels and confounders was conducted. Out of 404 included patients, 89 patients had an unfavorable outcome. Mean mRS on admission as well as 3 months post-stroke was 2 (±1). Low IGF-1 levels (day 8) were independently associated with a decreased risk of an unfavorable outcome (OR 0.61; 95%CI 0.37–0.99; p=0.044). Low IGFBP-3 levels (day 8) were independently associated with an unfavorable outcome (OR 2.75; 95%CI 1.56–4.84; p<0.001). Low IGFBP-3 levels and high IGF-1 levels in the subacute phase are predictive of unfavorable outcome 3 months after stroke.
Keywords: neuroprotection; acute cerebral infarction; modified Rankin Scale